RESPONS ANAK-ANAK MIGRAN TERHADAP MIGRASI INTERNASIONAL DI PERDESAAN PONOROGO - Sri Purwatiningsih (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2016)
Children being left behind by their parents whose migrating are vulnerable to face social problems. Several studies noted the negative impact on migration on the children, but some positive impact on the household prosperity were gained as well. Even though it has the negative impact, international migration has an increasing tendency to become one of the efforts to boost the household economy. This article uses data from CHAMPSEA (Child Health and Migrant Parents in South East Asia) Study which underlined the importance to know the child’s condition as the impact of international migration phenomena towards the family they left behind. Study showed that children being left by migrated parents, especially fathers, gave more positive responses, but those being left by mothers or both of the parents gave more negative responses. Nevertheless, those children apparently had desire to do migration abroad just as their parents did. Apparently the surrounding of the migrants and the better economy of migrant households had in uenced the children to do migration and work abroad as well.